2022
DOI: 10.1108/ijchm-07-2021-0954
|View full text |Cite
|
Sign up to set email alerts
|

Cocreating food experience “delivered” from iconic local restaurants

Abstract: Purpose This study aims to explore an emerging phenomenon – gourmet meal kits delivered to out-of-towners from iconic local restaurants. This study explores the interplay of goal framing and basic needs and their effects on customer intentions. This study also examines the underlying mechanism of experience cocreation and the moderating effect of food involvement. Design/methodology/approach This study develops a framework that combines the self-determination theory (SDT) and customer experience cocreation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…However, the TPB gives way to the creation of more comprehensive models by incorporating different constructs (Ajzen, 1991). For this reason, more comprehensive studies can be conducted within the context of local food consumption intention by incorporating constructs such as food motivations (Leung et al , 2022), food neophobia (Richards, 2021; Shi et al , 2022), food awareness and food involvement (Dedeoğlu et al , 2022). Moreover, responsible tourist behavior may have a multidimensional structure.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…However, the TPB gives way to the creation of more comprehensive models by incorporating different constructs (Ajzen, 1991). For this reason, more comprehensive studies can be conducted within the context of local food consumption intention by incorporating constructs such as food motivations (Leung et al , 2022), food neophobia (Richards, 2021; Shi et al , 2022), food awareness and food involvement (Dedeoğlu et al , 2022). Moreover, responsible tourist behavior may have a multidimensional structure.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…They are also offering abbreviated takeout menus and family meals and selling wines from the cellar, which allow customers to enjoy a fine dining experience in the comfort of their own homes. A recent study showed that delivering gourmet meal kits to out-of-towners will increase consumers’ intention to visit the independent local restaurant (Leung et al , 2022). Furthermore, participants indicated that financial incentives, such as discounts, are more important for them to order from upscale/fine dining restaurants than from casual dining restaurants.…”
Section: Discussionmentioning
confidence: 99%
“…Consumers' perceived ability to use technology and their evaluation of its usefulness drive their behavioral intentions Davis (1989) 13 Huang, Chang, et al, 2019;Izogo & Jayawardhena, 2018;Kim et al, 2021;Liang & Liu, 2019;Liao et al, 2010;Liu et al, 2016;McCormick & Livett, 2012;Mohamed et al, 2014;Morgan-Thomas & Veloutsou, 2013;Pantano & Priporas, 2016;Shams et al, 2020;Sun et al, 2022) Service-Dominant Logic and Cocreation Theory According to service-dominant logic a service ecosystem is considered to be a selfcontained, self-adjusting system of resourceintegrating actors that are interconnected by shared institutional logics and create mutual value through service exchange. Cocreation occurs through an iterative process involving all actors, which is guided by shared institutional logics and goes beyond the traditional firm-customer dyad Lusch (2004, 2008) 6 (Anshu et al, 2022;Blasco-Arcas et al, 2014;Elsharnouby & Mahrous, 2015;Lei et al, 2022;Leung et al, 2022;Zhang et al, 2017) Customer Engagement Theory…”
Section: Stimulus-organism-response (S-o-r) Modelmentioning
confidence: 99%